Understanding User Acceptance of Mobile Investment Applications: A Study of Pluang Through the Modified Technology Acceptance Model - Rifki, Wananda Muhammad; Puspita, Niniek Fajar; Taufik, Tatang Akhmad (Management Analysis Journal, 2025)
"Pluang" is a mobile investment innovation product featuring various assets such as gold, stocks, cryptocurrency, mutual funds, and indices. Initially introduced to the public in 2019, its adoption saw significant growth over the first three years. However, concerns emerged as user growth slowed down and complaints escalated due to perceived burdensome product innovations. Consequently, ensuring sustained adoption across diverse user groups necessitates immediate implementation of enhanced management strategies. This study aims to identify influential factors in adopting "Pluang," including reputation, self-efficacy, usage behavior, innovation, attitude toward use, intention to use, and ease of use using the Modified Technology Acceptance Model (M-TAM). Purposive sampling gathered responses from at least 200 users considering twice the minimum data required for variable interactions and anticipating data errors during processing. Analyzed via PLS-SEM (Partial Least Square - Structured Equation Modeling), the study revealed six significant correlations among nine hypotheses—particularly involving reputation, innovation, self-efficacy—and user attitudes toward use. These findings stress the importance of boosting application reputation, promoting continuous innovation, and optimizing training/promotional campaigns for better conversion of positive attitudes into strong usage intentions